2021
DOI: 10.1088/1741-4326/ac38c9
|View full text |Cite
|
Sign up to set email alerts
|

Energy confinement in the spherical tokamak Globus-M2 with a toroidal magnetic field reaching 0.8 T

Abstract: The work presents the results of the energy confinement study carried out on the compact spherical tokamak (ST) Globus-M2 with toroidal magnetic field (BT) as high as 0.8 T. A reproducible and stable discharge was obtained with the average plasma density (5-10) 1019 m-3. Despite the increase in the magnetic field, the neutral beam injection (NBI) led to clear and reproducible transition to the H-mode accompanied by a decrease in the turbulence level at the plasma edge. NBI allowed effectively heat the plasma: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The absolute value of Z eff was in the range 2-2.5 according to the measured bremsstrahlung radiation intensity [16] and verified by ASTAR simulations comparing the calculated and measured loop voltage. Estimated effective ion heat diffusivity χ i values were as high as 1.5-3 m 2 s −1 that is similar to the electron heat diffusivity (χ i = χ e ) and it is 2-3 times higher than the neoclassical ion heat diffusivity values [12].…”
Section: Energy Confinementmentioning
confidence: 69%
See 1 more Smart Citation
“…The absolute value of Z eff was in the range 2-2.5 according to the measured bremsstrahlung radiation intensity [16] and verified by ASTAR simulations comparing the calculated and measured loop voltage. Estimated effective ion heat diffusivity χ i values were as high as 1.5-3 m 2 s −1 that is similar to the electron heat diffusivity (χ i = χ e ) and it is 2-3 times higher than the neoclassical ion heat diffusivity values [12].…”
Section: Energy Confinementmentioning
confidence: 69%
“…From the figure, one can see that observed τ E rise cannot be explained using strong τ E dependence on plasma current only. Accurate analysis of the τ E dependence on I p and B T was recently reported [5,12]. It has been shown that both I p and B T increase, enhancing energy confinement, while the role of B T is more important.…”
Section: Energy Confinementmentioning
confidence: 99%
“…After the transition to H-mode, an increase in the plasma density was followed by the rise of the total stored energy W DIA , measured by the diamagnetic loop. Compared to the experiments on Globus-M, carried out with a magnetic field of 0.4 T, the total stored energy increased by a factor of four [ 10 ]. The h-factor also changes after the LH transition and increases from 0.5 to 1.2–1.4, which is the result of the energy confinement time τ E in H-mode doubling and reaching 7 ms.…”
Section: Lh Transition and H-mode On Globus-m2mentioning
confidence: 99%
“…It is worthy of note that all of the aforementioned tokamaks differ in parameters and yet still show a similar dependence on the magnetic field, which contradicts the conventional τ E,98y,2 scaling [ 8 ]. It was also determined that there seems to be a strong correlation between the increase in energy confinement time and the decrease in collisionality, which is seen as an indication of favorable plasma parameters for the future [ 10 ]. All this leads to the question of what other properties of the H-mode or the LH transition deviate in spherical tokamaks in comparison to more conventional devices.…”
Section: Introductionmentioning
confidence: 99%
“…This NSTX-Petty08 scaling formula is a continuous function of ε but is not unique and has considerable physics uncertainty. Obtaining a more definitive low-A confinement scaling [13,14] at reduced collisionality and higher magnetic field and current is a major research goal for NSTX-U [15][16][17][18][19][20], MAST-U [21][22][23], ST-40 [24], and Globus-M2 [25].…”
Section: Fusion Pilot Plant Performance Projectionsmentioning
confidence: 99%